Historical Perspectives on Democracies and their Adversaries
XIII, 297 p. 1 illus.
Keywords: This book historicizes the debate over how democratic regimes deal with anti-democratic groupings in society. Democracies across the world increasingly find themselves under threat from enemies, ranging from terrorists to parties and movements that undermine democratic institutions from within. This compilation of essays provides the first historical exploration of how democracies have dealt with such anti-democratic forces in their midst and how this impacted upon what democracy meant to all involved. From its inception in the nineteenth century, modern democratic politics has included fundamental debates over whether it is undemocratic and dangerous to ban parties with anti-democratic objectives and whether democracies should defend themselves, if necessary with violence, against perceived anti-democratic forces. This volume shows that implicit conceptions of democracy and democratic repertoires become explicit, fluid, and contested throughout these confrontations, not only withindemocratic parties, but also among their adversaries. Both sides have, at times, used force or limited the expression of ideas, thus blurring the lines between who is democratic and who is not. .